2015
DOI: 10.1186/s13561-015-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

The Nigeria wealth distribution and health seeking behaviour: evidence from the 2012 national HIV/AIDS and reproductive health survey

Abstract: BackgroundRecently, Nigeria emerged as the largest economy in Africa and the 26th in the world. However, a pertinent question is how this new economic status has impacted on the wealth and health of her citizens. There is a dearth of empirical study on the wealth distribution in Nigeria which could be important in explaining the general disparities in their health seeking behavior. An adequate knowledge of Nigeria wealth distribution will no doubt inform policy makers in their decision making to improve the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Our findings on the effect of neighbourhood SES on the likelihood that children of an educated mother have SAM are in consonance with existing findings [36,37]. These studies showed that the odds of better health outcomes are higher among residents in high socioeconomic areas than persons who reside in socioeconomically disadvantaged areas [36,37]. It is therefore important that the countries with high SAM and high pro-illiterate inequalities in SAM rework their child nutrition policies by taking a cue from countries with a low SAM and low pro-literate inequalities.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on the effect of neighbourhood SES on the likelihood that children of an educated mother have SAM are in consonance with existing findings [36,37]. These studies showed that the odds of better health outcomes are higher among residents in high socioeconomic areas than persons who reside in socioeconomically disadvantaged areas [36,37]. It is therefore important that the countries with high SAM and high pro-illiterate inequalities in SAM rework their child nutrition policies by taking a cue from countries with a low SAM and low pro-literate inequalities.…”
Section: Discussionsupporting
confidence: 92%
“…A proxy for socio-economic status was constructed using an asset-based wealth index to capture longer-term wealth [24], as has been used before in studies on health care in low-income countries [25,26]. The wealth index is based on the first factor loading of a principal component analysis of a large set of asset variables and housing characteristics, including details on the housing situation (such as home ownership status, quality of walls, number of rooms, sanitation), durable assets (such as numbers of TVs, fridges, paraffin lamps, bicycles), machinery (irrigation equipment, ploughs, tractors etc.)…”
Section: Methodsmentioning
confidence: 99%
“…This is very intuitive because females, irrespective of social status, can be enticed with little monetary gifts by older male partners and get initiated to sexual activities unlike the males. We used adolescents' and youths' economic status as proxies for their parents' economic status which has been found to be correlated with parents' education and sexual risky behaviour among adolescents and young adults 26,41 . This indicated that economical means of parents do not influence timing of sexual debut in their female children unlike among males.…”
Section: Discussionmentioning
confidence: 99%